PERANAN SUBSEKTOR PERKEBUNAN TEMBAKAU DALAM PEREKONOMIAN KABUPATEN MAGELANG - Nurhidayah, Intan Wahyu; Puspitaningrum, Dwi Aulia; Widayanto, Budi (Jurnal Ilmu-Ilmu Agribisnis, 2025)
Magelang Regency, located in Central Java Province possesses significant potential in various sectors, especially in tobacco cultivation. This study aims to analyze the contribution of tobacco products to the plantation sub-sector in Magelang Regency, analyze the sub-districts as the basis for tobacco products in Magelang Regency, and mapping the sub-districts that have the potential for the tobacco sub-sector in Magelang Regency. A quantitative method was used for this research. This research used secondary data sourced from Badan Pusat Statistik (BPS) of Magelang Regency. Documentation and interviews were conducted as data collection methods. The data analysis technique used in this study consisted of a contribution analysis, Location Quotient (LQ) analysis, Dynamic Location Quotient (DLQ) analysis, and Geographic Information System (GIS) analysis with ArcGIS. The results show that in 2017, the contribution of tobacco products to the plantation sub-sector in Magelang Regencies reached 50.7% and recorded as the highest value compared to other years. The sub-districts that are the basis (LQ≥1) for the tobacco commodity are Sawangan, Kaliangkrik, Windusari, Pakis, and Ngablak. Prospective sub-districts (DLQ≥1) are Borobudur, Ngluwar, Salam, Srumbung, Shaman, Sawangan, Candimulyo, Kajoran, Windusari, Tegalrejo, Pakis, and Grabag Sub-district. The mapping results show that Pakis Sub-district is the most potential sub-district for tobacco commodities. Keywords : contribution, potential, role, tobacco commodities